Prácticas de enseñanza de profesores universitarios que orientan la clase de biología y ecología para estudiantes de ingeniería de la universidad Antonio Nariño. flor Mariela cuervo Páez universidad Antonio Nariño facultad de educación maestría en educación Bogotá, D. C., noviembre de 2016 - Cuervo Páez, Flor Mariela (Universidad Antonio Nariño, 2023)
The basic foundation of this research that was carried out during the second semester of 2016 was focused on knowing some elements related to the teaching practices of university professors who guide the Biology and Ecology class for integrated groups of engineering students (civil, systems and mechatronic, industrial, environmental, electromechanical, control and industrial automation computing), from the Antonio Nariño University.